Respuesta :

Answer:

80 < 93 < 121 < 127

Step-by-step explanation:

For a geometric series,

[tex]\sum_{t=1}^{n}a(r)^{t-1}[/tex]

Formula to be used,

Sum of t terms of a geometric series = [tex]\frac{a(r^t-1)}{r-1}[/tex]

Here t = number of terms

a = first term

r = common ratio

1). [tex]\sum_{t=1}^{5}3(2)^{t-1}[/tex]

   First term of this series 'a' = 3

   Common ratio 'r' = 2

   Number of terms 't' = 5

   Therefore, sum of 5 terms of the series = [tex]\frac{3(2^5-1)}{(2-1)}[/tex]

                                                                      = 93

2). [tex]\sum_{t=1}^{7}(2)^{t-1}[/tex]

   First term 'a' = 1

   Common ratio 'r' = 2

   Number of terms 't' = 7

   Sum of 7 terms of this series = [tex]\frac{1(2^7-1)}{(2-1)}[/tex]

                                                    = 127

3). [tex]\sum_{t=1}^{5}(3)^{t-1}[/tex]

    First term 'a' = 1

    Common ratio 'r' = 3

    Number of terms 't' = 5

   Therefore, sum of 5 terms = [tex]\frac{1(3^5-1)}{3-1}[/tex]

                                                 = 121

4). [tex]\sum_{t=1}^{4}2(3)^{t-1}[/tex]

    First term 'a' = 2

    Common ratio 'r' = 3

    Number of terms 't' = 4

    Therefore, sum of 4 terms of the series = [tex]\frac{2(3^4-1)}{3-1}[/tex]

                                                                       = 80

    80 < 93 < 121 < 127 will be the answer.

Answer:

first is the one with 4 and 2(3) then 5 and 3(2) then 5 and 3 then 7 and 2

Step-by-step explanation: